Resilience measurement model in public spaces, based on the City Resilience Index - Cabrera Andrade, Paola Lizbeth (Centro Universitario de Arte, Arquitectura y Diseño, 2020)
The City Resilience Index is an urban resilience measurement instrument; structured in four dimensions, twelve goals as a target and fifty-two indicators, it forms a tool that is measured at the city level. Public spaces are actors that constitute and structure, they are also considered complex and vulnerable elements; resilience is a primary feature to be developed, as a means of dealing with impacts and stresses, through applied scaling. Documentary compilation, which supports the selection and subsequent adaptation of indicators; its review and analysis for the escalation proposal enables the comprehensive assessment of public space from a resilient perspective; a methodological approach to its evaluation is determined by developing analysis questions, solved in coded scenarios for quantitative valuation; measurement and data collection tools, for tabulation and resilience profiling.